Diagnóstico da gestão de resíduos da construção civil no município de Toledo/PR a partir da análise do descarte em caçambas estacionárias - Lima, Hildner de (2018)
The construction sector is one of the economic poles that most impact on the environment when it comes to solid waste. This is due to the high volume generated, which generate management problems because they are discarded and deposited irregularly in most of the Brazilian municipalities, intensifying the problems of sanitation and contamination of the soil in urban areas. Most of the problems involved are due to the fact that, at the beginning of the chain, the generator carries out the disposal of Civil Construction Waste (RCC) mixed with other materials that could be reused. In this sense, the present research focuses on the collection of data relevant to this stage, analyzing the deposition of solid waste in stationary buckets of two companies in the city of Toledo / PR. Through the investigation of the contents of these buckets, parameters, nonconformities and in the generation, transportation and destination processes. The methodology consisted of a bibliographical research and data collection in the field, besides the application of mixed method, considering the treatment of qualitative and quantitative data. The results show that, in construction or renovation works, there is no separation of waste regardless of size of the project, stage of the work or type of generator. In general, the waste management is not effective, since the generator does not worry about adequately allocating the volume generated, there is access from third parties in the process and in most cases there is the disposal of waste in quantities greater than allowed (out of the buckets). In addition, companies that carry out transportation and final destination of the waste, collect material even if improperly disposed and non-conforming to current legislation. It is estimated that the inspection is not enough to curb these infractions and there is no awareness on the part of companies and society as to the adequate disposition and the possibility of reuse of the waste generated.